Seasonal distribution and interactions between plankton and microplastics in a tropical estuary. (5th November 2015) - Lima, A.R.A.; Barletta, M.; Costa, M.F.
Abstract: The seasonal migration of a salt wedge and rainfall were the major factors influencing the spatiotemporal distribution of ichthyoplankton and microplastics along the main channel of the Goiana Estuary, NE Brazil. The most abundant taxa were the clupeids Rhinosardinia bahiensis and Harengula clupeola, followed by the achirid Trinectes maculatus (78.7% of the catch). Estuarine and mangrove larvae ( e.g . Anchovia clupeoides, Gobionellus oceanicus ), as well as microplastics were ubiquitous. During drier months, the salt wedge reaches the upper estuary and marine larvae ( e.g . Cynoscion acoupa ) migrated upstream until the zones of coastal waters influence. However, the meeting of waterfronts in the middle estuary forms a barrier that retains the microplastics in the upper and lower estuary most part of the year. During the late dry season, a bloom of zooplankton was followed by a bloom of fish larvae (12.74 ind. 100 m −3 ) and fish eggs (14.65 ind. 100 m −3 ) at the lower estuary. During the late rainy season, the high freshwater inflow flushed microplastics, together with the biota, seaward. During this season, a microplastic maximum (14 items 100 m −3 ) was observed, followed by fish larvae maximum (14.23 ind. 100 m −3 ) in the lower estuary. In contrast to fish larvae, microplastics presented positive correlation with high rainfall rates, being more strictly associated to flushing out/into the estuary than to seasonal variation in environmental variables. Microplastics represented half of fish larvae density. Comparable densities in the water column increase the chances of interaction between microplastics and fish larvae, including the ingestion of smaller fragments, whose shape and colour are similar to zooplankton prey. Graphical abstract: Highlights: Salt wedge and rainfall influenced the distribution of plankton and microplastics. Microplastics represented half of fish larvae density. High freshwater inflow flushed microplastics and the biota seaward. Interactions between microplastics and fish larvae are increasing. Ingestion of microplastics might cause gut blockage and induce starvation.